The usage of life and health insurance products in financial planning process. - Henny Ramali. (2008)
The objective of this study is to highlight the importance of Life and Health Insurance in accomplishing one’s financial plans. The motivation behind this study is based on the fact that most people are still unaware of the usefulness of Life and Health Insurance products in the planning process.